Emerging therapeutic approaches for Tourette syndrome and other tic disorders: a systematic review of current clinical trials - Häge, Alexander; Krämer, Robert; Dunlap, Michele; Mechler, Konstantin; Müller-Vahl, Kirsten R.; Nagy, Peter (European child & adolescent psychiatry, 2024)
Tourette syndrome and other tic disorders are prevalent neurodevelopmental disorders typically treated with behavioral techniques or pharmacological interventions, primarily antipsychotics. However, many patients do not achieve sufficient response to conventional treatments, underscoring the need for further research in this area. To provide a comprehensive overview of ongoing research activities, we systematically searched the clinical registries of the World Health Organization (WHO) and of the United States National Institutes of Health (NIH) for currently planned or ongoing registered clinical studies. Our search identified 21 registered studies, of which seven focus specifically on pharmacological interventions. Potential candidates include the dopamine D1 antagonist ecopipam, the phosphodiesterase inhibitor gemlapodect, and cannabis-based therapies. Additionally, several studies are exploring behavioral interventions including Comprehensive Behavioral Interventions for Tics (CBIT) and mindfulness training, neurostimulation including MRI-navigated transcranial stimulation, theta burst stimulation, and deep brain stimulation, traditional Chinese medicine, and other approaches such as microbiota transplantation. Despite the range of research activities underway, the overall landscape remains limited. In this report we will discuss the findings, current developments, and relevant aspects concerning future research including clinical, scientific, and patient perspectives.